Preparation method and application of oxygen-enriched titanate nanotube material with visible light catalytic performance
By preparing oxygen-rich titanate nanotube materials, the problem of low efficiency of traditional photocatalysts in the treatment of antibiotic pollutants is solved, and the efficient photocatalytic removal effect is achieved. It is suitable for pharmaceutical wastewater treatment. The material is low in cost and pollution-free. , simple operation characteristics.
Patent Information
- Application Number
- CN202411276730.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-20
AI Technical Summary
Traditional photocatalysts have low photocatalytic degradation efficiency of antibiotic pollutants, low solar light utilization efficiency and low photo quantum yield, making it difficult to effectively deal with antibiotic pollution in pharmaceutical wastewater.
The oxygen-rich titanate nanotube material is prepared by hydrothermal and stirring. The surface is rich in peroxy groups, expanding the light absorption range to the visible light area, forming a multi-layer tubular structure, with paramagnetic and high-efficiency photocatalytic properties .
It significantly improves the photocatalytic removal rate of antibiotics and the efficiency of photocatalysts, and can efficiently remove antibiotics under visible light. Its degradation effect is better than that of traditional titanate nanotubes and commercial titanium dioxide. It has low material cost, no pollution, simple operation, and is suitable for large-scale Production.
Smart Images

Figure CN119158560A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment, and in particular relates to a preparation method and application of an oxygen-enriched titanate nanotube material with visible light catalytic performance. Background Art
[0002] Updates in analytical techniques have enabled more and more pollutants to be accurately identified, including perfluorinated compounds, endocrine disruptors, pharmaceuticals and personal care products, carcinogenic polycyclic aromatic hydrocarbons, brominated flame retardants and other toxic substances. Antibiotics, as the most important emerging organic pollutant, have attracted attention because of their increasing consumption, widespread presence in the environment, and the development and spread of antibiotic resistance. Antibiotics can enter the environment through a variety of pathways, including industrial services, hospitals, aquaculture facilities, runoff from fields to surface water, and runoff to soil through animal husbandry and manure application. Pharmaceutical wastewater and hospital sewage are the main sources of antibiotic pollution, especially pharmaceutical wastewater, which has the characteristics of large organic pollutant load, high salinity, and large shock load. Antibiotics may cause various environmental and health risks in the long term, such as increasing the resistance of exposed microorganisms, and may enter aquatic organisms to produce toxic side effects, and their own resistance and toxicity to non-target organisms, especially antibiotic resistance, have become an imminent global health threat, seriously threatening ecosystems and human health, so the problem of pharmaceutical wastewater treatment of antibiotics has attracted widespread attention at home and abroad.
[0003] Due to the difficult biodegradation of antibiotic pollutants, it is difficult to effectively remove them by conventional secondary sewage treatment processes. The adsorption method can only achieve the enrichment of drugs, but cannot fundamentally degrade drug molecules, cannot achieve toxicity reduction, and there is a risk of secondary pollution during the regeneration of the adsorbent. In membrane technology, microfiltration membranes and ultrafiltration membranes have large pore sizes and are generally used to remove suspended matter and microorganisms in water. They cannot directly and effectively intercept and separate active drug molecules; nanofiltration and reverse osmosis membranes are expensive, and the membranes are easily contaminated during application. In contrast, photocatalytic technology is green and energy-saving, and can directly use sunlight to purify the environment; the reaction conditions are mild, and pollutants can be degraded at room temperature, especially toxic and difficult-to-degrade organic pollutants; it is safe and has no secondary pollution, and pollutants can be completely oxidized and decomposed into harmless products such as CO2 and H2O; it is broad-spectrum and long-lasting, and almost hundreds of pollutants can be degraded, and the catalyst can be used for a long time. However, there are problems of low light energy utilization and low quantum efficiency. Therefore, one of the current research hotspots is the development of photocatalysts that absorb visible light.
[0004] Titanate nanomaterials have attracted more and more attention due to their uniform tubular microstructure, large specific surface area, rich functional groups (-ONa / -OH), good ion exchange performance, high solution stability and high photoelectric quantum conversion effect, thus showing great application potential in the environmental field. However, there are also problems such as low light absorption and UV response. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of low photocatalytic degradation efficiency of traditional photocatalysts for antibiotic pollutants, low sunlight utilization efficiency and / or low photon yield. To this end, the present invention provides a method for preparing an oxygen-rich titanate nanotube material with visible light catalytic performance and a method for using the same to remove antibiotic pollutants in pharmaceutical wastewater and hospital sewage.
[0006] The present invention firstly provides an oxygen-rich titanate nanotube material with visible light catalytic performance. The oxygen-rich titanate nanotube has an average diameter of 8 to 15 nm, an average inner diameter of 2 to 5 nm, and a nanotube length of 50 to 80 nm.
[0007] In one embodiment of the present invention, the surface of the oxygen-rich titanate nanotube material is rich in peroxide groups, which can extend the ultraviolet-responsive titanate nanotubes to absorb in the visible region.
[0008] In one embodiment of the present invention, the oxygen-rich titanate nanotubes present a multi-layer tubular structure.
[0009] In one embodiment of the present invention, the oxygen-rich titanate nanotubes have paramagnetism, and characteristic signals of superoxide species can be obtained by electron paramagnetic resonance spectrometer testing.
[0010] In one embodiment of the present invention, the oxygen-rich titanate nanotubes have visible light catalytic performance.
[0011] In one embodiment of the present invention, the oxygen-rich titanate nanotubes have the characteristics of uniform morphology, good stability, large specific surface area, and strong visible light absorption capacity, which endow the photocatalyst with the ability to efficiently remove antibiotics under visible light.
[0012] The present invention also provides a method for preparing the above oxygen-rich titanate nanotube material with visible light catalytic performance, comprising the following steps:
[0013] (1) mixing titanium dioxide and NaOH in a solvent and performing a hydrothermal reaction, cooling, washing and drying to obtain a titanate nanotube material;
[0014] (2) The titanate nanotubes obtained in step (1) are mixed with peroxide in a solvent and stirred, and then washed and dried to obtain an oxygen-rich titanate nanotube material having visible light catalytic performance.
[0015] In one embodiment of the present invention, in step (1), the titanium dioxide is any one or more of anatase and rutile crystal types of titanium dioxide, preferably P25 type titanium dioxide.
[0016] In one embodiment of the present invention, in step (1), the solvent is water.
[0017] In one embodiment of the present invention, the mass ratio of titanium dioxide to solvent water is 1:50 to 1:100, and the mass ratio of titanium dioxide to NaOH is 1:5 to 1:30.
[0018] In one embodiment of the present invention, in step (1), the concentration of NaOH is in the range of 1 to 15 mol / L.
[0019] In one embodiment of the present invention, in step (1), the mixing process includes stirring for 4 to 24 hours after ultrasonic dispersion. Furthermore, the mixing process is preferably carried out at room temperature, and the room temperature is preferably 10 to 40°C.
[0020] In one embodiment of the present invention, in step (1), the hydrothermal reaction is preferably carried out in a reactor, and the reactor is preferably a reactor lined with polytetrafluoroethylene.
[0021] In one embodiment of the present invention, in step (1), the hydrothermal reaction is carried out at 120-180° C. for 36-72 hours.
[0022] In one embodiment of the present invention, in step (1), the washing and drying includes a process of solid-liquid separation, washing and drying. The solid-liquid separation may be any means in the art that can separate the solid phase and the liquid phase, such as membrane filtration, etc.; the washing preferably uses anhydrous ethanol washing; the drying includes oven drying or freeze drying.
[0023] Furthermore, in step (1), the washing and drying preferably includes: using a suction filtration device covered with a 0.25 μm hydrophilic filter membrane to perform suction filtration, collecting the intercepted product, repeating 4-5 times, and then using anhydrous ethanol for dispersion washing, repeating 2 times, collecting the prepared material after solid-liquid separation, and drying at 60-100°C for 24 hours to obtain titanate nanotubes.
[0024] In one embodiment of the present invention, in step (2), the stirring is carried out at 10 to 35° C. for 5 to 24 hours.
[0025] In one embodiment of the present invention, in step (2), the peroxide is a compound containing a peroxy group -OO-, including one or more of hydrogen peroxide, peroxy acid salts, and organic peroxides; preferably one or both of hydrogen peroxide and persulfate.
[0026] In one embodiment of the present invention, in step (2), the solvent is water.
[0027] In one embodiment of the present invention, in step (2), the concentration of the peroxide is 0.01 to 0.5 mol / L, and the molar ratio of titanate nanotubes to peroxide is 0.01 to 1.0.
[0028] In one embodiment of the present invention, in step (2), the washing and drying includes a process of solid-liquid separation, washing and drying. The solid-liquid separation can be any means in the art that can separate the solid phase and the liquid phase, such as membrane filtration, etc.; the washing is preferably washed with anhydrous ethanol; and the drying is oven drying.
[0029] The present invention also provides the use of the above oxygen-rich titanate nanotube material with visible light catalytic performance in wastewater treatment.
[0030] In one embodiment of the present invention, preferably, the wastewater contains antibiotic pollutants, and more preferably, the wastewater contains fluoroquinolone antibiotic pollutants.
[0031] In one embodiment of the present invention, the wastewater includes but is not limited to pharmaceutical wastewater and hospital sewage.
[0032] The present invention also provides a method for removing antibiotics from water, wherein the method utilizes the oxygen-rich titanate nanotube material with visible light catalytic performance as a photocatalyst to catalytically degrade the antibiotics.
[0033] In one embodiment of the present invention, the dosage of the oxygen-rich titanate nanotube material with visible light catalytic performance is 0.1 to 2.0 g / L; the initial concentration of the antibiotic pollutant solution in water is 1 to 100 mg / L.
[0034] In one embodiment of the present invention, the pH of the aqueous solution is 2 to 12, preferably 3-11, and more preferably 3-9.
[0035] Compared with the prior art, the present invention has the following advantages:
[0036] The present invention is a method for preparing and using an oxygen-rich titanate nanotube material with visible light catalytic performance. The raw materials of the material are titanium dioxide, sodium hydroxide, hydrogen peroxide and persulfate. The synthesis method is completed by hydrothermal method and stirring method. It has the characteristics of low cost, no pollution, simple operation, etc., and is suitable for large-scale production. Compared with traditional commercial photocatalysts, oxygen-rich titanate nanotubes are based on titanate nanotubes. Through surface oxidation etching with hydrogen peroxide or persulfate, the obtained material has abundant peroxide active sites on its surface, which extends the light absorption range of titanate nanotubes to the visible light region. The prepared adsorbent has more active sites and stronger photocatalytic efficiency, and can be widely used in industries such as wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a physical picture of the oxygen-rich titanate nanotube material prepared in Example 1;
[0038] Figure 2 This is a TEM image of the oxygen-rich titanate nanotube material prepared in Example 1;
[0039] Figure 3 The degradation kinetics of gatifloxacin by P25 commercial titanium dioxide, titanate nanotubes and oxygen-enriched titanate nanotubes in experimental example 1 under simulated sunlight;
[0040] Figure 4 The degradation kinetics of gatifloxacin by P25 commercial titanium dioxide, titanate nanotubes and oxygen-enriched titanate nanotubes in Experimental Example 1 under visible light;
[0041] Figure 5 The degradation kinetics of gatifloxacin by the oxygen-rich titanate nanotube material at different pH values in Experimental Example 3;
[0042] Figure 6 The degradation kinetics of gatifloxacin by the oxygen-rich titanate nanotube material at different ionic strengths in Experimental Example 4;
[0043] Figure 7 The degradation kinetics of gatifloxacin by the oxygen-rich titanate nanotube material under the concentration of humic acid in Experimental Example 5;
[0044] Figure 8 This is the degradation kinetics of different antibiotics (gatifloxacin, ciprofloxacin, sulfamethoxazole, cefadroxil, and tetracycline) by the oxygen-rich titanate nanotube material in Experimental Example 2. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below with reference to examples. The examples are only intended to illustrate the present invention and do not limit the scope of application of the present invention.
[0046] Example 1
[0047] Material preparation:
[0048] (1) 1.2 g of P25 titanium dioxide and 29 g of sodium hydroxide were added to 65 mL of deionized water for ultrasonic dispersion and stirred at room temperature for 12 h;
[0049] (2) The uniformly mixed solution in step 1 was transferred to a polytetrafluoroethylene-lined reactor, reacted in an oven at 130° C. for 72 h, and then naturally cooled to room temperature;
[0050] (3) The product was mixed with 500 mL of deionized water, stirred thoroughly, and filtered using a suction filtration device with a hydrophilic filter membrane with a pore size of 0.22 μm to collect the intercepted product. This was repeated 4-5 times, and the product was dispersed in anhydrous ethanol and dried in an oven at 80° C. for 12 h to obtain white titanate nanotubes.
[0051] (4) 0.5 g (1.66 mmol) of titanate nanotubes were dispersed in 100 mL of 0.1 mol / L hydrogen peroxide solution, ultrasonically dispersed, and stirred at room temperature for 6 h;
[0052] (5) The obtained product is filtered, washed and dried, and the obtained yellow sample is the oxygen-rich titanate nanotube material.
[0053] Experimental Example 1
[0054] Material application: Study on the photocatalytic removal of gatifloxacin under simulated sunlight and visible light using P25 commercial titanium dioxide (Degussa, Germany), titanate nanotubes (prepared in steps (1) to (3) of Example 1), and oxygen-rich titanate nanotubes (prepared in steps (4) to (5) of Example 1).
[0055] The concentration of gatifloxacin was 5 mg / L. 100 mL of the solution was placed in a conical flask, and 0.1 g / L of P25 commercial titanium dioxide, titanate nanomaterials, and oxygen-enriched titanate nanotube materials were added and mixed evenly. HCl or NaOH was used to adjust the pH to 5.0. The reactor was placed under a xenon lamp (Microsolar 300, Perfil) using the simulated sunlight mode (AM 1.5). A magnetic rotor was added and the speed was set to 500 rpm. The irradiation intensity was 100 mW / cm 2 , the external circulating cooling water system ensures that the reaction temperature is 25°C. Take out 1 mL of the mixed solution with a pipette at the selected time point, and immediately filter the mixed solution using a syringe and a 0.22 μm PTFE membrane, and store the filtered clear solution in a liquid phase vial. The concentration of gatifloxacin was measured by high performance liquid chromatography, and the removal rate of gatifloxacin by different photocatalysts was calculated:
[0056] (C0 is the initial concentration of gatifloxacin, C t is the concentration of gatifloxacin at time point t).
[0057] Specific as Figure 3 As shown, it can be seen that the oxygen-rich titanate nanotubes prepared by the present invention can achieve efficient photocatalytic removal of gatifloxacin under simulated sunlight within 90 minutes, and the removal rate of gatifloxacin by the material is as high as 99% under the premise of extremely low material dosage. In comparison, the removal rates of gatifloxacin by P25 type titanium dioxide and titanate nanotubes are less than 50%. In addition, the reaction rate constant of the oxygen-rich titanate nanotube material is as high as 0.055min -1 , which is much higher than 0.006min of P25 commercial titanium dioxide and titanate nanotubes. -1 and 0.009min -1 . It can be seen that the oxygen-rich titanate nanotube material of the present invention has better photocatalytic performance than commercial titanium dioxide and titanate nanotubes, more efficient carrier separation efficiency, and is more conducive to electron transfer between active oxygen species and organic pollutants. Intuitively, the color of the oxygen-rich titanate nanotubes changes from white to yellow. The reason is that more hydroxyl groups are added to the surface of the material, which increases the range of the absorption spectrum. Compared with commercial titanium dioxide and titanate nanotubes, oxygen-rich titanate nanotubes have higher valence band potentials on the one hand, and the holes they can produce are more oxidizing; on the other hand, they have narrower bandgap widths, and more electrons are easily excited by photons to transition, generating more active free radicals, thereby improving the efficiency of photocatalytic degradation of water pollutants.
[0058] Experimental Example 2
[0059] Material application: Catalytic degradation kinetics of gatifloxacin by oxygen-rich titanate nanotube materials under visible light
[0060] The concentration of gatifloxacin was 5 mg / L. 100 mL of the solution was placed in a conical flask. 0.1 g / L of P25 commercial titanium dioxide, titanate nanomaterials and oxygen-enriched titanate nanotube materials were added and mixed evenly. HCl or NaOH was used to adjust the pH to 5.0. The reactor was placed under a xenon lamp (Microsolar 300, Perfil). A visible light filter (400-800 nm) was used to cut off the ultraviolet light. A magnetic rotor was added and the speed was set to 500 rpm. The irradiation intensity was 100 mW / cm 2, the external circulating cooling water system ensures that the reaction temperature is 25°C. 1 mL of the mixed solution was taken out with a pipette at the selected time point, and the mixed solution was immediately filtered using a syringe and a 0.22 μm PTFE membrane, and the filtered clear liquid was stored in a liquid phase vial. The concentration of gatifloxacin was measured by high performance liquid chromatography, and the removal rate of gatifloxacin by different photocatalysts was calculated.
[0061] Specific as Figure 4 As shown, it can be seen that the oxygen-rich titanate nanotubes prepared by the present invention can achieve more than 60% efficient photocatalytic removal of gatifloxacin under visible light within 90 minutes. In contrast, the removal rates of gatifloxacin by P25 type titanium dioxide and titanate nanotubes are less than 10%. In addition, the reaction rate constant of the oxygen-rich titanate nanotube material is as high as 0.014min -1 , which is much higher than 0.00min of P25 commercial titanium dioxide and titanate nanotubes -1 . The reaction rate of oxygen-rich titanate nanotubes is 14 times that of original titanate nanotubes. It can be seen that oxygen-rich titanate nanotubes greatly expand the absorption in the visible region, and the valence band potential of titanate nanotubes increases from 2.81eV to 2.96eV. Therefore, the oxidation ability of holes generated in the valence band of oxygen-rich titanate nanotubes after being excited by photons is stronger than that of pure titanate nanotubes. Oxygen-rich titanate nanotubes not only increase visible light absorption, but also enhance carrier migration and capture capabilities, and reduce the consumption of carrier recombination.
[0062] Experimental Example 3
[0063] Material application: Degradation kinetics of gatifloxacin by oxygen-rich titanate nanotube materials at different pH values
[0064] The gatifloxacin concentration was 5 mg / L. 100 mL of the solution was placed in a conical flask. 1 g / L of the oxygen-enriched titanate nanotube material obtained in Example 1 was added and mixed evenly. HCl or NaOH was used to adjust the pH to 3.0, 5.0, 7.0, 9.0, and 11.0. The reactor was placed under a xenon lamp (Microsolar 300, Perfil) using simulated sunlight mode and visible light mode, respectively. A magnetic rotor was added and the speed was set to 500 rpm. The irradiation intensity was 100 mW / cm 2 , the external circulating cooling water system ensures that the reaction temperature is 25°C. 1 mL of the mixed solution was taken out with a pipette at the selected time point, and the mixed solution was immediately filtered using a syringe and a 0.22 μm PTFE membrane, and the filtered clear liquid was stored in a liquid phase vial. The concentration of gatifloxacin was measured by high performance liquid chromatography, and the removal rate of gatifloxacin by different photocatalysts was calculated.
[0065] As the pH value increases from 3.0 to 11.0, the photocatalytic degradation effect of oxygen-rich titanate nanotubes on gatifloxacin gradually decreases, and the photocatalytic reaction rate also decreases synchronously. Figure 5 As shown. Under simulated sunlight, gatifloxacin at all pH values is degraded to more than 85%, especially under acidic conditions, the degradation rate is more than 98% within 90 minutes; under visible light conditions, the degradation rate is also more than 40%, and 100% removal of gatifloxacin can be achieved by extending the time and increasing photocatalysis. It can be seen that the oxygen-rich titanate nanotube material of the present invention can achieve a photocatalytic degradation effect on gatifloxacin at a pH of 3.0-11.0, and preferably, it is most suitable for sewage and wastewater treatment processes in the pH range of 3 to 7.
[0066] Experimental Example 4
[0067] Material application: Degradation kinetics of gatifloxacin by oxygen-rich titanate nanotube materials at different ionic strengths
[0068] The gatifloxacin concentration was 5 mg / L. 100 mL of the solution was placed in a conical flask. 0.1 g / L of the oxygen-enriched titanate nanotube material obtained in Example 1 was added and mixed evenly. 0.1, 0.5, 1.0, and 5 mmol / L of NaCl, CaCl2, and FeCl3 were added, respectively. HCl or NaOH was used to adjust the pH to 5.0. The reactor was placed under a xenon lamp (Microsolar 300, Perfil), using the simulated sunlight mode (AM1.5). A magnetic rotor was added and the speed was set to 500 rpm. The irradiation intensity was 100 mW / cm 2 , the external circulating cooling water system ensures that the reaction temperature is 25°C. 1 mL of the mixed solution was taken out with a pipette at the selected time point, and the mixed solution was immediately filtered using a syringe and a 0.22 μm PTFE membrane, and the filtered clear liquid was stored in a liquid phase vial. The concentration of gatifloxacin was measured by high performance liquid chromatography, and the removal rate of gatifloxacin by different photocatalysts was calculated.
[0069] At low concentrations, Na + and Ca 2+ The addition of Ca had no significant effect on the photocatalytic activity of oxygen-rich titanate nanotubes. However, when the ion concentration was increased to 5 mmol / L, a slight inhibitory effect was found, and the degradation rate of gatifloxacin decreased by 15%, of which Ca 2+ The inhibitory effect is more obvious, such as Figure 6 In contrast, Fe 3+ The addition of Fe greatly promoted the degradation efficiency. The degradation rate of gatifloxacin could reach 100% within 90 minutes. 3Participates in the electron transfer process on the catalyst surface and promotes the separation of charge carriers. In summary, the oxygen-rich titanate nanotube material of the present invention has good resistance to competition with coexisting cations in water, and can adsorb more target organic pollutants in the presence of ions to promote degradation, proving that the material involved in the present invention will have better practical application prospects.
[0070] Experimental Example 5
[0071] Material application: Photocatalytic removal performance of oxygen-rich titanate nanotube materials on gatifloxacin at different humic acid concentrations
[0072] Photocatalytic removal of organic pollutants from water bodies needs to consider the competitive adsorption and free radical quenching of natural organic matter in water. Photocatalysts must have strong resistance to competitive adsorption and quenching of natural organic matter. Example Humic acid was used to represent natural organic matter for simulation experiments. Gatifloxacin was 5 mg / L. 100 mL of solution was placed in a conical flask. 0.1 g / L of the oxygen-enriched titanate nanotube material obtained in Example 1 was added and mixed evenly. 1, 5, 10, and 20 mg / L of humic acid were added respectively. HCl or NaOH was used to adjust the pH to 5.0. The reactor was placed under a xenon lamp (Microsolar 300, Perfil), using simulated sunlight mode and visible light mode. A magnetic rotor was added and the speed was set to 500 rpm. The irradiation intensity was 100 mW / cm 2 , the external circulating cooling water system ensures that the reaction temperature is 25°C. 1 mL of the mixed solution was taken out with a pipette at the selected time point, and the mixed solution was immediately filtered using a syringe and a 0.22 μm PTFE membrane, and the filtered clear liquid was stored in a liquid phase vial. The concentration of gatifloxacin was measured by high performance liquid chromatography, and the removal rate of gatifloxacin by different photocatalysts was calculated.
[0073] Natural organic matter, as a common component in natural water bodies, sewage, and wastewater, will compete with target pollutants in the water for active sites. The concentration of natural organic matter in sewage is much higher than the concentration of new pollutants, so it will lead to a decrease in the degradation rate of photocatalytic materials. Humic acid, as a representative type of natural organic matter in water, is often used to verify whether a water treatment process has practical application value. In general water bodies, the concentration of humic acid is about 1 to 20 mg / L. The specific experimental results are as follows Figure 7As shown. Under simulated sunlight, the 90-minute removal rate of gatifloxacin by oxygen-rich titanate nanotube material was as high as 99% when humic acid was not added. When the humic acid concentration increased from 0 to 5 mg / L, its adsorption of gatifloxacin only decreased by 16%. Even under extreme conditions, when the humic acid concentration was 20 mg / L, the oxygen-rich titanate nanotube material still maintained a photocatalytic removal rate of 65%. Under visible light, the inhibition increased with the increase of humic acid concentration, especially when the humic acid concentration was 20 mg / L, the removal rate decreased by 29%. Humic acid competes for the adsorption sites of pollutants on the one hand, and consumes active species as a quencher of free radicals on the other hand, thereby reducing the photocatalytic effect. In summary, oxygen-rich titanate nanotube materials have good ability to resist the inhibition of natural organic matter in water.
[0074] Experimental Example 6
[0075] Material application: Photocatalytic removal of various antibiotics by the oxygen-rich titanate nanotube material prepared in Example 1
[0076] Ciprofloxacin, sulfamethoxazole, cefadroxil, and tetracycline were selected as representative antibiotic pollutants to test the photocatalytic removal ability of oxygen-rich titanate nanotube materials. The experiment used the same experimental method as Experimental Example 1, and the pollutant concentration analysis was performed using high performance liquid chromatography. The experimental results are shown in Figure 2. Figure 8 As shown. Under 90 minutes of simulated sunlight, the removal rates of the four pollutants by oxygen-rich titanate nanotubes were all above 90%, among which the removal rates of ciprofloxacin and sulfamethoxazole reached 99%. In summary, the oxygen-rich titanate nanotube material has an outstanding effect on the removal of antibiotic pollutants.
[0077] Example 2
[0078] Material preparation:
[0079] (1) Add 2.5 g of P25 titanium dioxide and 15.0 g of sodium hydroxide into 100 mL of deionized water for ultrasonic dispersion and stir at room temperature for 6 h;
[0080] (2) The uniformly mixed solution in step 1 was transferred to a polytetrafluoroethylene-lined reactor, reacted in an oven at 150° C. for 36 h, and then naturally cooled to room temperature;
[0081] (3) The product was mixed with 500 mL of deionized water, stirred thoroughly, and filtered using a suction filtration device with a hydrophilic filter membrane with a pore size of 0.22 μm to collect the intercepted product. This was repeated 4-5 times, and the product was dispersed in anhydrous ethanol and dried in an oven at 80° C. for 12 h to obtain white titanate nanotubes.
[0082] (4) 1.0 g (3.32 mmol) of titanate nanotubes were dissolved in 100 mL of 0.15 mol / L hydrogen peroxide solution, ultrasonically dispersed, and stirred at room temperature for 8 h;
[0083] (5) The obtained product is filtered, washed and dried, and the obtained yellow sample is the oxygen-rich titanate nanotube material.
[0084] The photocatalytic performance of the oxygen-rich titanate nanotube material prepared in this embodiment was measured according to the method of Experimental Example 1. It was found that under simulated sunlight, the oxygen-rich titanate nanotube achieved a removal rate of more than 95% of gatifloxacin in 90 minutes, and the reaction rate constant was as high as 0.049 min -1 .
[0085] According to the method of Experimental Example 3, the test was conducted and it was found that the oxygen-rich titanate nanotube material of this embodiment is suitable for wastewater treatment processes within a pH range of 3 to 9.
[0086] According to the method of Experimental Example 4, it was found that Na + , Ca 2+ The photocatalytic effect of the oxygen-rich titanate nanotube material of this embodiment is not significantly affected. 3+ When the concentration increased from 0 to 5 mmol / L, the removal efficiency of the material for gatifloxacin increased.
[0087] Example 3
[0088] Material preparation:
[0089] (1) 3.5 g of P25 titanium dioxide and 20.0 g of sodium hydroxide were added to 200 mL of deionized water for ultrasonic dispersion and stirred at room temperature for 8 h;
[0090] (2) The uniformly mixed solution in step 1 was transferred to a polytetrafluoroethylene-lined reactor, reacted in an oven at 180° C. for 24 h, and then naturally cooled to room temperature;
[0091] (3) The product was mixed with 400 mL of deionized water, stirred thoroughly, and filtered using a suction filtration device with a hydrophilic filter membrane with a pore size of 0.22 μm to collect the intercepted product. This was repeated 4-5 times, and the product was dispersed in anhydrous ethanol and dried in an oven at 90° C. for 12 h to obtain white titanate nanotubes.
[0092] (4) 0.5 g (1.66 mmol) of titanate nanotubes were dispersed in 100 mL of 0.2 mol / L hydrogen peroxide solution, ultrasonically dispersed, and stirred at room temperature for 12 h;
[0093] (5) The obtained product is filtered, washed and dried, and the obtained yellow sample is the oxygen-rich titanate nanotube material.
[0094] The photocatalytic performance of the oxygen-rich titanate nanotubes prepared in this embodiment was measured according to the method of Experimental Example 1. It can be found that under simulated sunlight, the oxygen-rich titanate nanotube material can achieve efficient removal of gatifloxacin in 90 minutes, and under the premise of extremely low material dosage, the removal rate of gatifloxacin by the material is as high as more than 95%.
[0095] According to the method of Experimental Example 3, the test was conducted and it was found that the oxygen-rich titanate nanotube material of this embodiment is suitable for wastewater treatment processes within a pH range of 3 to 9.
[0096] According to the methods of Experimental Examples 4 and 5, it was found that Na + and Ca 2+ The adsorption effect of the composite material of this embodiment was not greatly affected. When the HA concentration increased from 0 to 20 mg / L, the photocatalytic removal rate of gatifloxacin by the material decreased by 14%.
[0097] Comparative Example 1
[0098] During the preparation of titanate nanotubes, key parameters such as the type of titanium dioxide, the concentration of sodium hydroxide, the hydrothermal reaction temperature and duration are all related to the interlayer structure, Ti-O coordination mode, titanium oxide octahedral arrangement, specific surface area, surface functional group distribution and other properties of titanate nanotubes, and ultimately affect the photocatalytic performance and practical value of oxygen-rich titanate nanotube materials.
[0099] For example, when anatase, rutile, and P25 titanium dioxide are used as raw materials to prepare titanate nanotubes, the remaining parameters and steps are the same as in Example 2, and the photocatalytic effect of the titanate nanotubes prepared using anatase and rutile as raw materials is reduced. Among them, P25 titanium dioxide can form an internal heterojunction during the hydrothermal process to promote the photocatalytic effect. According to the determination method of Example 2, it was found that within 90 minutes, the photocatalytic removal rate of gatifloxacin by oxygen-enriched titanate nanotubes using anatase and rutile as raw materials was only 85% and 73%.
[0100] For another example, when P25 titanium dioxide is used as a raw material, if the sodium hydroxide concentration is lower than 2 mol / L, the remaining parameters and steps are the same as those in Example 2, and the final prepared titanate nanotubes are not fully curled and are easily hydrolyzed, thereby affecting the photocatalytic performance. According to the determination method of Example 2, it is found that the photocatalytic removal rate of gatifloxacin within 90 minutes is only 61%, which is 34% lower than that of Example 2.
[0101] For another example, when the hydrothermal temperature is lower than 120°C and the duration is lower than 12 hours, it is impossible to prepare titanate nanotubes with stable structural morphology (the remaining steps and parameters are the same as in Example 1). The hydrothermal conditions will be directly related to the morphology of the titanate in the composite material, and even affect the adsorption performance of the composite material. The main reason is that under the method of hydrothermal treatment at 120 to 180°C for 36 to 72 hours, the titanate nanotubes exist in a hollow tubular form (tube length 50 to 80 nanometers) with an outer diameter of 8 to 10 nanometers and an inner diameter of 2 to 5 nanometers. This structure greatly promotes the adsorption of various organic pollutants through the pore size selection effect and capillary absorption effect. If the heating time and temperature are not properly matched, the above-mentioned tubular structure cannot be formed.
[0102] For example, when heated at 120°C for 6 hours, the titanate nanotube material will exist in the structure of two-dimensional nanosheets. In another example, when heated at 220°C for 96 hours, the titanate will be converted into a solid rod-like structure, and the length of each single rod is less than 50 nanometers. The final photocatalytic ability of the oxygen-rich titanate nanotube material is only similar to that of titanium dioxide, which is far lower than that of the material prepared under the optimal synthesis conditions.
[0103] In addition, it was found through testing that when the hydrogen peroxide in step (4) of Examples 1 to 3 is replaced by peroxy acid salts or organic peroxides, oxygen-rich titanate nanotube materials can also be prepared, and their performance is similar to that of the corresponding Examples 1 to 3.
[0104] Comparative Example 2
[0105] After the successful preparation of titanate nanotubes, it is necessary to oxidize in a hydrogen peroxide solution to form surface peroxide groups, wherein the concentration of hydrogen peroxide will be directly related to the number of active sites in the oxygen-rich titanate nanotube material, and even affect the photocatalytic performance of the material. In the synthesis process of oxygen-rich titanate nanotubes, if the concentration of hydrogen peroxide is lower than 0.01 mol / L, the surface oxidation is not sufficient, the active sites are insufficient, and the visible light catalytic effect is affected. Under simulated sunlight, the removal rate of gatifloxacin in 90 minutes is only 71%; when the concentration of hydrogen peroxide is higher than 0.5 mol / L, the surface oxidation sites are sufficient, but homogeneous decomposition is prone to occur, affecting the separation and transmission of carriers. Compared with the material prepared in Example 1, its removal rate of gatifloxacin is only 82%, which is 13% lower than that in Example 2, and the resistance to humic acid is significantly reduced, and the removal rate is reduced by 27% under normal environmental concentration (humic acid concentration 10 mg / L).
[0106] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. An oxygen-rich titanate nanotube material with visible light catalytic performance, characterized in that: The average diameter of the oxygen-rich titanate nanotubes is 8 to 15 nm, the average inner diameter is 2 to 5 nm, and the length of the nanotubes is 50 to 80 nm.
2. The oxygen-rich titanate nanotube material with visible light catalytic performance according to claim 1, characterized in that: The oxygen-rich titanate nanotubes present a multi-layer tubular structure.
3. The method for preparing an oxygen-rich titanate nanotube material having visible light catalytic performance according to claim 1 or 2, characterized in that: The following steps are involved: (1) mixing titanium dioxide and NaOH in a solvent and performing a hydrothermal reaction, cooling, washing and drying to obtain a titanate nanotube material; (2) The titanate nanotubes obtained in step (1) are mixed with peroxide in a solvent and stirred, and then washed and dried to obtain an oxygen-rich titanate nanotube material having visible light catalytic performance.
4. The preparation method according to claim 3, characterized in that: In step (1), the titanium dioxide is any one or more of anatase and rutile crystal types of titanium dioxide. The preparation method according to claim 3, characterized in that in step (1), the mass ratio of titanium dioxide to NaOH is 1:5 to 1:
30.
5. The preparation method according to claim 3, characterized in that: In step (1), the hydrothermal reaction is carried out at 120-180° C. for 36-72 hours.
6. The preparation method according to claim 3, characterized in that: In step (1), the peroxide is a compound containing a peroxy group -OO-, including one or more of hydrogen peroxide, peroxy acid salts, and organic peroxides.
7. The preparation method according to claim 3, characterized in that: In step (2), the concentration of the peroxide is 0.01 to 0.5 mol / L, and the molar ratio of titanate nanotubes to peroxide is 0.01 to 1.
0.
8. Use of the oxygen-rich titanate nanotube material with visible light catalytic performance as claimed in claim 1 or 2 or the material prepared by the preparation method as claimed in any one of claims 3 to 7 in wastewater treatment.
9. The use according to claim 8, characterized in that: The wastewater contains antibiotic pollutants.
10. A method for removing antibiotics from water, characterized in that: The method utilizes the oxygen-rich titanate nanotube material with visible light catalytic performance as claimed in claim 1 or 2 or the material prepared by the preparation method as claimed in any one of claims 3 to 7 to catalytically degrade antibiotics.
